Medical Physics - Voto Bernales, Juan (1925)
Medical Physics is to study the physical phenomena that occur in the body and exert action on the agents. It also addresses the manner taught natural agents in the study and exploration of the human body and in the way in the same agents for use in the treatment of disease can be used.